Crystallization of The Quran: An Analysis of John Wansbrough’s Theory - Ahmad Sanusi Azmi (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2017)
In the early nineteenth century, modern scholars began to explore materials of Quranic studies within the framework of a historical-critical method. Novel arguments were presented in challenging the traditional account of the formation of the Quran with a various range of theory. It seems that the most radical assessment was demonstrated by John Wansbrough in his exceptional works, Quranic Studies: Sources and Methods of Scriptural. The literary analysis employed by John Wansbrough in his study on the Quran lead to a novel historic inference. This article aims to explore the theory of late crystallization of the Quran as proposed by John Wansbrough. This study is the qualitative research in which the researcher uses the study of the comparative text analysis. The resulting study asserts that Wansbrough’s theory is a new discovery which has given the new impact and the new path in the Quranic studies. His conclusion is not accepted by all scholars. Some scholars regarded Wansbrough’s evidence that he used as an argument is not absolutely convincing.